Association between common allergens and symptoms among allergic rhinitis patients in HUSM - Ashari, Noor Suryani Mohd (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2010)
Allergic rh1nit1s 1s the mo$'1 common allerg1c d1sease affecting an estimated four m1lhon people in Malaysia. · Althqugh this disease is not usually severe disease, it significantly alters the social life of patients and affects school learning performance as well as work productivity. This study was done to determine levels of allergen specific Immunoglobulin E assay, in allergic rhinitis patients in Hospital Universiti Sains Malaysia (HUSM), Malaysia and to determine the severity of symptoms before proceed with evaluation of possible association between this parameter with severity of allergic rhinitis. In this cross sectional study, total and specific lgE to 28 types of allergens were measured in serum samples from 128 allergic rhinitis patients. The interviewer guided questionnaire was used to evaluate the severity of symptoms using ARIA criteria. In this study we found that Dermatogoides farinae (97%) was the most common allergen. Regarding the symptoms, sneezing (99.2%) was found to be the most common clinical symptoms. We also found a significant association between the specific lgE levels and the severity of allergic rhinitis for Dermatogoides farinae (p=0.024), Dermatogoides pteronyssinus (p=.039), cockroach (p = 0.038) cat (p = 0.042) and latex (p = 0.044) .